Cipro: le sfide per i giovani in un paese diviso - Baracani, Elena (SocietàMutamentoPolitica, 2012)
The case of Cyprus shows that modalities of state-building and decisions taken at the beginning of this process may favor the politicization of ethnicity, and thus the emergence of a political conflict. This happens especially when other factors are present, such as certain ethnic characteristics of the social tissue. This essay aims at reconstructing the main phases of state-building until the accession of the island to the European Union, while showing how state-building, ethnicity, and external factors interact and influence each other. The essay also presents some socio-demographic and political attitudes data of young Cypriots in order to reconstruct their perceptions of national political institutions and of the process of European integration.